Sugar transporters in higher plants - A diversity of roles and complex regulation - Sauer, Norbert; et al. (Trends in Plant Science, 2000)
Sugar-transport proteins play a crucial role in the cell-to-cell and long-distance distribution of sugars throughout the plant. In the past decade, genes encoding sugar transporters (or carriers) have been identified, functionally expressed in heterologous systems, and studied with respect to their spatial and temporal expression. Higher plants possess two distinct families of sugar carriers: the disaccharide transporters that primarily catalyse sucrose transport and the monosaccharide transporters that mediate the transport of a variable range of monosaccharides. The tissue and cellular expression pattern of the respective genes indicates their specific and sometimes unique physiological tasks. Some play a purely nutritional role and supply sugars to cells for growth and development, whereas others are involved in generating osmotic gradients required to drive mass flow or movement. Intriguingly, some carriers might be involved in signalling. Various levels of control regulate these sugar transporters during plant development and when the normal environment is perturbed. This article focuses on members of the monosaccharide transporter and disaccharide transporter families, providing details about their structure, function and regulation. The tissue and cellular distribution of these sugar transporters suggests that they have interesting physiological roles.